Realities and expectations of young Indonesian workers in offshore oil and gas industry - Harahap, Aswin Syapii; Yosepha, Sri Yanthy (Goodwood Publishing, 2025)
Purpose: This study aims to explore the gap between work expectations and actual workplace realities from the perspective of young Indonesian workers in the offshore oil and gas industry, focusing on how such discrepancies affect job satisfaction, psychological well-being, and organizational loyalty. Research Methodology: An exploratory qualitative approach was employed, involving semi-structured in-depth interviews with 15 offshore workers aged 22–35, located in Natuna and the Java Sea. The data were analyzed using thematic analysis framework, which enabled systematic identification of recurring themes related to expectations, psychological stress, and retention. Results: Findings reveal that young workers’ expectations are shaped by media portrayals and institutional narratives that glamorize offshore work. However, the realities long shifts, isolation, and psychological strain often lead to disillusionment. Many participants experienced cognitive dissonance, reduced job satisfaction, and a strong intention to resign. The study also uncovered a psychological entrapment phenomenon, where workers remained not out of satisfaction but due to a lack of viable alternatives. Conclusions: The Expectation-Disconfirmation Theory and Psychological Contract Theory effectively explain the disconnect between expectations and job experiences. In offshore contexts, misalignment can significantly impact worker loyalty and mental health. Limitations: The study is limited in sample size (15 participants) and geographic scope (Natuna and Java Sea). It also lacks managerial or HR perspectives, restricting organizational-level analysis. Contribution: This study offers practical implications for HR management in high-risk industries, emphasizing realistic recruitment, mental preparedness, and integrated psychological support. It also contributes novel insights into the concept of psychological entrapment in early-career professionals.